2005
DOI: 10.1200/jco.2005.07.048
|View full text |Cite
|
Sign up to set email alerts
|

Peer-Delivered Smoking Counseling for Childhood Cancer Survivors Increases Rate of Cessation: The Partnership for Health Study

Abstract: Interventions to prevent future illnesses are of critical importance to childhood cancer survivors. The Partnership for Health intervention resulted in a doubling of smoking cessation quit rates. Because of the seriousness of smoking among childhood cancer survivors, this intervention model may be appropriate as a multicomponent treatment program for survivors who smoke.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
135
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(137 citation statements)
references
References 28 publications
2
135
0
Order By: Relevance
“…No assessments of improvements in knowledge of the effect of smoking on health or smoking cessation strategies were measured, despite these being the main component of the information given in the interventions. However, Emmons 2005 26,97 reported that most participants found the written material useful or very useful. Rates of participation and attrition can be used as surrogate markers for the acceptability of a programme.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No assessments of improvements in knowledge of the effect of smoking on health or smoking cessation strategies were measured, despite these being the main component of the information given in the interventions. However, Emmons 2005 26,97 reported that most participants found the written material useful or very useful. Rates of participation and attrition can be used as surrogate markers for the acceptability of a programme.…”
Section: Discussionmentioning
confidence: 99%
“…The promotora and participant reviewed past quit attempts, discussed the pros and cons of smoking and quitting, discussed self-monitoring to identify smoking patterns, identified potential reinforcements and substitute behaviours and discussed appropriate coping strategies, set a quit date, discussed experiences while quitting and relapse prevention, and talked about overall lifestyle change. In Emmons 2005 26,97 the intervention emphasised the smoker's choice, personal responsibility for change and enhancement of self-efficacy. The calls were tailored to the participants' stage of readiness to quit smoking and interest in other health topics and goals.…”
Section: Main Activitiesmentioning
confidence: 99%
“…Self-efficacy was assessed with a question about the participants' level of confidence that they could quit smoking in 1 month. 11 …”
Section: Methodsmentioning
confidence: 99%
“…The definition of a current smoker employed in this study was intended to capture even occasional smokers 32 because young cancer survivors tend to be lighter smokers, and any level of smoking can be harmful to the survivor's health. 7,11 Eligible survivors were invited to participate in a randomized controlled trial evaluating the effectiveness of PFH-2, an internetbased version of the Partnership for Health (PFH) study, a survivor-focused smoking cessation intervention. 33,34 This paper presents baseline data from survivors who agreed to participate in the trial; study design is provided in detail elsewhere.…”
Section: Participantsmentioning
confidence: 99%
“…If baseline self-efficacy and readiness to change are controlled than the same cohort group is twice as more likely to achieve cessation than self-help group. 45 In a mental health setting with adults with serious psychiatric illness, peer support interventions had the highest outcomes. 46 It should also be noted that, lack of social support, puts an individual at a greater risk for depression.…”
Section: Role Of a Peer Support On Tobacco Cessationmentioning
confidence: 99%